Structural and functional evaluation of oxygenating keratin/silk fibroin scaffold and initial assessment of their potential for urethral tissue engineering. (April 2016) - Lv, XiangGuo; Li, Zhe; Chen, ShiYan; Xie, MinKai; Huang, JianWen; Peng, XuFeng; Yang, RanXing; Wang, HuaPing; Xu, YueMin; Feng, Chao
Abstract: In this study, we report a new type of oxygen-generating scaffold, composed of human keratin, silk, gelatin and calcium peroxide (CPO). After mixing the silk/keratin (60:40) with 2% gelatin and 20% CPO, the film demonstrated excellent mechanical properties, non-cytotoxicity and oxygen-generative ability. The detailed structure of scaffold was revealed by confocal laser and electronic scanning microscopy. The gelatin formed the network structure, which mixed with silk fibroin and keratin. The CPOs were embedded into scaffold. A shell–core structure was formed in the CPO particles, in which the CPO was located in the core and the gelatin was mainly wrapped around the CPO. Furthermore, the oxygen-release test showed that scaffold was able to steadily release high level of oxygen over two weeks in vitro. In addition, the anti-bacterial function was also proved in the scaffold. Films with CPO enhanced the repair in dog urethral defect models, resulting in patent urethra. Improved organized muscle bundles and epithelial layer were observed in animals treated with CPO films compared with those treated with non-CPO films. This study suggests that this biomaterial could be suitable for tissue engineered urinary tract reconstruction.